Association of oral pathology, oral microbiology, and oral oncology - Sri Lokaranjan, Divya; Ravi, Kamalam; Choudhary, Susmita; Talukdar, Anindita; Dandekeri, Shilpa; Shunmugavelu, Karthik (GMS Hygiene and Infection Control)
An ecological community of commensals, symbiotic and pathogenic organisms share our body space. Alterations in the ecologically balanced population of microflora result in dysbiosis and are critical determinants of systemic health and diseases, especially in the context of immunosuppression. The oral microbiome and chronic inflammation may have a role in carcinogenesis.